Convergence in Income Inequality - Panizza, Ugo (Journal of Income Distribution®, 2001)
This paper uses OLS and GMM estimations to test for convergence in income distribution. Convergence tests are performed using a high-quality U.S. cross-state panel. The results strongly support the hypothesis of convergence in income distribution across American states.